Ukraine Fiscal Incentives for Science, Technology and Innovation Activities : Good Practice Review Report - World Bank (World Bank, Washington, DC, 2017)
This report is one of four analytical pieces on Ukraine’s innovation and entrepreneurial ecosystem developed by the World Bank’s Ukraine Technical Assistance on Innovation, supported by the Swedish Ukraine Financial and Enterprise Sector Recovery and Growth Trust Fund. This report reviews different international good practices in introducing and implementing fiscal incentives for supporting science, technology, and innovation (STI) and provides policy recommendations relevant to the implementation of such incentives in Ukraine. It focuses on tax incentives as an indirect financial support mechanism for the private sector’s research and development (R&D) and innovation activity. It identifies the costs and benefits of a variety of fiscal incentives (six different regimes) to support STI that have been widely used worldwide. It is important to note that the good practice examples outlined in this report have all been implemented as part of a broader agenda for strengthening the science and technology base of the countries in which they were put in place. Each of the policies, in isolation, would not have been sufficient to achieve the objectives of the government. The report describes the Ukrainian context, focusing on the strengths and weaknesses of Ukraine’s science and technology base, followed by a discussion of the recent